2005
DOI: 10.1152/japplphysiol.00442.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinase-9 in endothelial apoptosis in chronic heart failure in mice

Abstract: . Role of matrix metalloproteinase-9 in endothelial apoptosis in chronic heart failure in mice. J Appl Physiol 99: [2398][2399][2400][2401][2402][2403][2404][2405] 2005. First published August 4, 2005; doi:10.1152/japplphysiol.00442.2005.-Accumulation of oxidized extracellular matrix between endothelium and muscle is an important risk factor in the endothelium-myocytes uncoupling in congestive heart failure. Although ventricular remodeling is accompanied by increased matrix metalloproteinase (MMP)-9 activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 30 publications
1
29
2
Order By: Relevance
“…Others and we previously suggested (12,19) a role of MMP activation and E-M uncoupling in cardiac remodeling and dysfunction in chronic heart failure. The results of this study showed that impaired arterial function in the HHcy model of arterial hy- Recently we demonstrated (20) that Hcy instigates a "negative vascular remodeling" or inward directed increase in arterial wall thickness and hypertension.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Others and we previously suggested (12,19) a role of MMP activation and E-M uncoupling in cardiac remodeling and dysfunction in chronic heart failure. The results of this study showed that impaired arterial function in the HHcy model of arterial hy- Recently we demonstrated (20) that Hcy instigates a "negative vascular remodeling" or inward directed increase in arterial wall thickness and hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…Twenty-five micrograms of total protein from aortic homogenates was loaded in each well, run on 10% SDS-PAGE, and transferred to polyvinylidene difluoride membranes. The membranes were blotted with anti-connexin 43 monoclonal antibodies (Chemicon) as previously described (19). Secondary IgG-alkaline phosphatase was used for detection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this, we inferred that H 2 S was indulged in mitigating proteolytic effect of MMPs caused by oxidative stress. ADAM-12 was a signal molecule downstream to proteinase-activated receptor-1 (PAR-1) that was involved in matrix remodeling (16). In AVF mice, ADAM-12 level increased but normalized after H 2 S treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TdT-mediated dUTP nick end labeling (TUNEL) assay was used to determine the number of apoptotic cells in the LV of 0 and 6 wk of AVF mice and 8 and 10 wk of H 2S-treated mice. LV tissues were snap-frozen following the procedure of Ovechkin et al (16) and labeled with TUNEL (Upstate Cell Signaling Solution, Lake Placid, NY) as per the instructions of the company. Cells were counted and scored from five randomly selected areas of each slide, and quantitative analysis was performed by employing Image-Pro Plus (Media Cybernetics, Silver Spring, MD).…”
Section: Methodsmentioning
confidence: 99%